Wańkowicz, Nobility, Borderlands and the State - Kopeć, Zbigniew (Porównania, 2025)
The subject of the author's interest is Melchior Wańkowicz’s reflections on the wealthy nobility living in the Eastern Borderlands (Kresy) during the pre-revolutionary period and in the Second Polish Republic. The analysis focuses on "Szczenięce lata" (“Puppy Years”) — a memoir from 1934 — as well as a series of reportage pieces titled "Znowu siejmy w Polsce B" (“Let Us Sow Again in Poland B”), published in the pro-government daily Kurier Poranny in 1937–1938. In these works, Wańkowicz presents both the past and present of the social class from which he originates. However, he emphasizes that he views the Kresy from the perspective of the State.